Analisis Jangka Panjang Fenomena Akuisisi Bytedance Terhadap Saham Terhadap Lanskap Industri Ekonomi Di Indonesia Dan Keamanan Negara - Aisyah Afinna Azharoh; Agus Wahyudi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This journal discusses the impact of TikTok's $1.5 billion USD acquisition of Tokopedia shares. Following the closure of TikTok Shop in Indonesia due to licensing issues, ByteDance (TikTok's parent company) re-entered the Indonesian e-commerce market through an investment in Tokopedia. This acquisition has sparked speculation about the collaboration and its impact on Indonesia's digital industry. Tokopedia will manage TikTok Shop in Indonesia, while TikTok will continue to operate as a social media platform. Concerns have arisen about potential monopoly and China's geopolitical influence, given ByteDance's close ties with the Chinese government. Issues of data ownership and security have also been highlighted as serious threats. This article emphasizes the importance of vigilance against foreign influence and its impact on Indonesia's economic sovereignty, drawing parallels to historical experiences such as the Trojan Horse, which illustrates the dangers of complacency.